Shape memory alloys for structural engineering: An editorial overview of research and future potentials. (15th December 2022) - Ghafoori, Elyas; Wang, Bin; Andrawes, Bassem
Abstract: In the past few decades, the modern design philosophy of structural engineering has gradually shifted from preventing building collapse and loss of lives to high-performance objectives. However, traditional construction materials (e.g., concrete, wood, and steel) may not meet some of the high-performance structural design objectives under extreme disasters. The increasing demand for high-performance objectives has motivated the exploration of advanced structural materials. As a special type of advanced metallic material, shape memory alloys (SMAs) have been developed vigorously toward structural engineering in recent years. SMAs can withstand large strains and still recover the initial shape via heating (i.e., shape memory effect) or unloading (i.e., superelasticity). Both properties have different application prospects in the construction sector. This Special Issue has collected 30 high-quality research articles that can be categorized into three different groups: material and mechanical behavior of SMAs, shape memory effect of SMAs for prestressing and strengthening of structures, and SMA-based devices for energy dissipation and self-centering earthquake-resilient structures. Through systematic analysis of the existing research studies, this editorial summarizes the current state of knowledge and suggests future research directions and potentials for SMAs in construction.